2011
DOI: 10.1016/j.ophtha.2010.11.022
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Components of Metabolic Syndrome and Open-Angle Glaucoma

Abstract: Purpose To determine whether an association exists between various components of metabolic syndrome (diabetes mellitus (DM), systemic arterial hypertension (HTN), hyperlipidemia, and obesity) and open-angle glaucoma (OAG) in a large, diverse group of individuals throughout the United States. Design Longitudinal cohort study. Participants All beneficiaries age ≥40 years continuously enrolled in a managed care network who had ≥1 visit to an eye care provider were identified from 2001–2007. Methods Billing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
159
7
10

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(199 citation statements)
references
References 48 publications
12
159
7
10
Order By: Relevance
“…52 In contrast, in the study by Pasquale et al, higher body mass index among women was associated with a lower risk of primary open-angle glaucoma with an IOP of 21 mm Hg or less at diagnosis. 53 The findings of other studies support the influence of low CSFP in glaucoma. Patients with slowly growing intracranial tumors close to the inner aperture of the optic nerve canal had an abnormally high prevalence of glaucomatous appearance of the optic nerve head.…”
Section: Clinical Observationssupporting
confidence: 59%
“…52 In contrast, in the study by Pasquale et al, higher body mass index among women was associated with a lower risk of primary open-angle glaucoma with an IOP of 21 mm Hg or less at diagnosis. 53 The findings of other studies support the influence of low CSFP in glaucoma. Patients with slowly growing intracranial tumors close to the inner aperture of the optic nerve canal had an abnormally high prevalence of glaucomatous appearance of the optic nerve head.…”
Section: Clinical Observationssupporting
confidence: 59%
“…Subjects with diabetes are more likely to develop eye disease, including retinopathy, macular edema, glaucoma, and cataracts [2,3]. Diabetic retinopathy, a consequence of chronic hyperglycemia, leads to substantial morbidity and is a major cause of new cases of legal blindness [3].…”
Section: Introductionmentioning
confidence: 99%
“…Through a rigorous searching process ( Supplementary Fig. S1), three relevant studies [3][4][5] were included in the final analysis (Supplementary Table S1). Pooled odds ratios demonstrated that hyperlipidemia did not increase the incidence of glaucoma (relative risk, 1.40; 95% confidence interval [CI], 0.73-2.68; Fig.…”
mentioning
confidence: 99%